Microlearning and microcredentials in Italy : strengthening workforce development and transparency - Angotti, Roberto [Verfasser]; Pedone, Alessandra [Verfasser] (My University, 2025)
„This article deals with the impact of digitalisation on Continuing Vocational Education and Training (CVET) in Italy, focusing on microlearning and microcredentials. The results of a company survey will be presented to provide insights into the prevalence of microlearning and the perceptions of companies and employees regarding its use. Finally, the article discusses the integration of micro-certificates into the Italian qualification system. The focus here is on the regulatory progress made in Italy with aligning micro-certificates to European standards.“ (authors‘ abstract; BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; S 1.5.2 Berufliche Weiterbildung; L 4.2.3 Internetbasiertes Lernen / E-Learning; L 2.1 Lernformen; 370; Berufliche Weiterbildung; Kompetenzentwicklung; Kompetenznachweis; E-Learning; Non-formales Lernen; Lernen und Arbeiten; Italien